My Strategy in PhD Application - Aziman, Abdullah (Faculty of Computer Systems and Software, 2013)
I believe all lecturers do have a dream or desire to pursue their study to PhD level. Some of us may still considering again and again either to do it or not. Some may rethinking either it is worth or not. But again, the ‘wanted PhD’ feeling is there in their mind and heart.